The Effect Of Mathematics Learning Approaches Realistic About Thinking Abilities Student Critical Response - San Febriyanti Simanjutakk; Lois Oinike Tambunan; Yanty Maria R. Marbun (STABN RADEN WIJAYA WONOGIRI, 2024)
SimanjutaThis study aims to determine the influence of the realistic mathematics learning approach on students' critical thinking skills at Taman Madya (Sma) Tamansiswa Pematangsiantar. This study uses a quantitative approach with an experimental research type. Experimental research is a way to find a causal relationship between two factors that are intentionally created by the researcher by eliminating or reducing or setting aside the factors of the approach. This research design is a form of illustration to facilitate the steps of problem solving or hypothesis testing. Judging from the objectives and hypotheses proposed, the form of research design used in this study is Quasi Experiment Post-test Only Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence of the Realistic Mathematics Learning Approach on critical thinking skills in Taman Madya (SMA) Tamansiswa Pematangsiantar. This influence can be seen from the regression equation = Y^^=-1.434+0.765X with a regression coefficient of 0.765 and a large determination coefficient of 94.8% which indicates that there is a positive relationship between the TTW type Cooperative learning model and problem-solving abilities